Y4Be33Pt16 – a non-centrosymmetric cage superconductor with multi-centre bonding in the framework. Issue 27 (25th June 2020) - Amon, Alfred; Svanidze, Eteri; Prots, Yurii; Nicklas, Michael; Burkhardt, Ulrich; Ormeci, Alim; Leithe-Jasper, Andreas; Grin, Yuri
Abstract : Y4 Be33 Pt16 – a novel non-centrosymmetric cage superconductor with multi-centre bonding in the framework. Abstract : The new ternary compound Y4 Be33 Pt16 was prepared from elements by arc melting, and its crystal structure was determined from single-crystal X-ray diffraction data (space group I 4̄3 d, a = 13.4849(3) Å). The material is the first representative of a new structure type of complex intermetallic compounds and reveals a cage-like crystal structure. Analysis of chemical bonding by means of the electron localizabilty approach indicates ionic interaction of yttrium with the rest of the crystal structure, characteristic for cage compounds, in particular for clathrates. In contrast to the mostly two-centre bonding in the framework of clathrates, the new compound is characterized by a multi-centre interaction within the framework, caused by the demand of the valence electrons in the system. The non-centrosymmetric material enters the superconducting state at T C = 0.9 K.